Correlation Between Dermatology Life Quality Index and Psoriasis Area and Severity Index in Patients with Psoriasis Treated with Ustekinumab - Jeanette Halskou Hesselvig; Alexander Egeberg; Nikolai Dyrberg Loft; Claus Zachariae; Kristian Kofoed; Lone Skov (Medical Journals Sweden, 2017)
Monitoring of biological treatment efficacy for psoriasis is based on clinical evaluation and patient's quality of life. However, long-term correlation between Psoriasis Area and Severity Index (PASI) and Dermatology Life Quality Index (DLQI) in real life has not been studied in patients treated with ustekinumab. All patients with psoriasis treated with ustekinumab at our department were included (n = 120) in this study. Correlation analyses between the change in PASI and DLQI and the individual subquestions in DLQI were performed using Spearman's rank correlation coefficient. A correlation value of 0.57 (p-value < 0.001) and 0.45 (p-value < 0.001) between PASI and DLQI were found in the period baseline - 4 months and baseline - 12 months, respectively. In DLQI subquestions, the greatest association was found for the questions on "Symptoms and feelings". Objective improvements in the severity of psoriasis were weakly to moderately associated with improvements in quality of life in patients with psoriasis treated with ustekinumab.